Publication Analysis on Supply and Demand Research: Mapping Future Research - Febriza, Milla; Rozalinda, Rozalinda; Zulvianti, Nora (Rangkiang: Journal of Islamic Economics and Business, 2025)
This study aims to map and analyze the development trends of research on the topic of "Supply and Demand" over the past decade, identifying gaps and providing directions for future investigation. Utilizing a quantitative bibliometric approach, data were collected from Scopus-indexed journal articles published between 2015 and 2024 using the Publish or Perish software, and analyzed through VOSviewer to visualize keyword relationships, author collaborations, and thematic evolution. The results indicate that while research on "Supply and Demand" has fluctuated annually, sustained scholarly interest persists, though only 138 relevant articles were found during this period, highlighting a relatively limited research volume. This presents both a challenge and an opportunity for deeper exploration. Notably, underexplored keywords such as platform, ecosystem service supply, demand response, customer, implication, and energy resources reveal emerging but insufficiently addressed areas within the literature. By mapping these specific gaps, this study offers a focused roadmap for future research to expand conceptual and methodological boundaries, encouraging scholars to integrate these under-investigated themes to generate novel, interdisciplinary, and contextually relevant insights in the field of Supply and Demand.